PELATIHAN BAHASA INGGRIS PADA ANAK DI PKBM HUDA WAN NUR - Allif Syahputra Bania; Imran; Nursamsu; Fadlia (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
PKBM Wan Nur prioritizes basic English learning for children. Children are the nation's future partners because with the possession of English skills, future leaders have inherited the procedures for communicating internationally in the era of globalization. The problems faced in the implementation of service activities are the increasing need for English language training for children, especially in PKBM Huda Wan Nur, the need for active coaching and socialization in fostering interest in learning English at PKBM Huda Wan Nur and the need for empowering positive mindsets for teachers about the importance of English for children. From the results of the study of the problems faced, the solutions that can be proposed to solve the existing problems are English language training for children at PKBM Huda Wan Nur and Increasing the empowerment of digital learning media in fulfilling interactive teaching materials for children at PKBM Huda Wan Nur. The implementation method is a field survey, scheduling, preparation, explanation, training, and evaluation. The children really enjoyed actively and seriously the basic English training activities related to nouns in the form of pictures of animals, fruits and flowers with bilingual texts that used teaching materials that could be obtained digitally.